TRANSPARANSI DATA, PRIVASI PELANGGAN, DAN KEPATUHAN REGULASI: ANALISIS KUALITATIF - Ahmad Jet Alamin A; Parlaban Karo-Karo; Robintang Elfrianto Naibaho (Jurnal Industri Kreatif dan Inovatif, 2025)
This study qualitatively examines the roles of data transparency, customer privacy, and regulatory compliance in maintaining customer trust and minimizing legal risks, particularly in the context of Indonesia’s Personal Data Protection Law (Law No. 27 of 2022 / UU PDP). In the digital era, data has become a strategic asset for companies, making transparent data governance and strong privacy protections essential for building market trust and responsible corporate governance. The research aims to analyze how data transparency contributes to trust, identify challenges in safeguarding customer privacy, and assess compliance mechanisms under the UU PDP to mitigate legal risks. Using document analysis and case studies, the findings indicate that consistent transparency enhances credibility, while privacy safeguards are crucial to prevent data misuse. The study recommends strengthening the integration of transparency practices, enhancing consumers’ rights regarding their data, and promoting collaboration among stakeholders to protect customer privacy and ensure adherence to the regulatory framework.